Recognition and localization of objects in relative scale for robotic applications - Md. Saiful Islam. (2008)
Three-dimensional object recognition and localization are the central problems for many applications of computer vision. Especially, for many robotic applications, it is necessary to recognize and localize the objects of interest in cluttered environment with high efficiency. Examples of such applications include object manipulation, visual inspection, surveillance system, and landmark localization for visual navigation. An object in different image planes could have undergone different kinds of geometric and photometric transformations. Moreover, the background could be cluttered with other objects and the objects of interest could be partially occluded. The recognition and localization methods should be robust to all such transformations and conditions.